Port Environmental Quality or Economic Growth? Their Relevance and Government Preference in Developing Countries - Tingliu Xu; Yingjie Xiao; Chatchai Khiewngamdee; Qin Lin (Discrete Dynamics in Nature and Society)
In the past few years, the marine ecosystem has been a cheap resource in developing countries in the process of pursuing short-term vested interests. Therefore, high economic development of the developing countries is at a huge environmental cost. Nowadays, environmental protection is becoming a global concern. In this background, the government of the developing countries begins to formulate reasonable marine economic and environmental policies to find a balance between rapid economic development and marine environmental protection. In this contribution, a dynamic stochastic general equilibrium model (DSGE) is constructed with the environmental constraints, and Bayesian estimation is used to calibrate the main parameters. Next, the model is employed to analyze the effects of government and consumer environmental preferences on macroeconomic variables, environmental quality, and consumer and government utility. Results show that the government’s preference for environmental quality is positively related to port environmental quality and negatively related to output, capital stock, and consumption. An enhancement of the environmental quality preference of the target audience can realize balanced development of economic growth and port environmental quality. The findings are conducive to coordinating the relationship between economic development and environmental protection and achieving sustainable development of the port.